Insect/Mite Management in Annona spp. - Jorge E. Peña; Jonathan H. Crane (EDIS, 2006)
ENY-834, a 5-page illustrated fact sheet by Jorge E. Pena and Jonathan H. Crane, addresses the major constraints to productivity of atemoya and sugar apple in Florida, key pests and lack of pollinating agents. Includes a table of insecticides registered for atemoya and sugar apple in Florida. Published by the UF Department of Entomology and Nematology, August 2006.